“Inclisiran: Early LDL-C target achievement in a real-life population” - Francesco Briani; Mauro Bagli; Gabriele Venturi; Francesco Bacchion; Antonio Mugnolo (Atherosclerosis Plus)
Background and objectives: Elevated low-density lipoprotein cholesterol (LDL-C) levels are associated with atherosclerotic cardiovascular diseases. Inclisiran, a small interfering RNA, has been observed to effectively and sustainably reduce LDL-C in large randomized controlled trials (RCTs); however, real-world data on its short-term efficacy and use are limited. This study aims to assess the efficacy and safety of inclisiran in a real-life population within one month from the first administration. Methods: This observational, single-center, retrospective cohort study included patients affected by dyslipidemia who could not achieve their LDL-C target despite a maximum tolerated oral lipid-lowering therapy (LLT). 284 mg Inclisiran was subcutaneously administered. Blood samples were collected before the inclisiran administration and at week and one month afterward with the aim toevaluate achievement of LDL-C targets at these time intervals (primary endpoint) and reduction in LDL-C levels (secondary endpoint). Results: From September 2022 to December 2023, inclisiran was administered to 33 patients at Mater Salutis Hospital. After exclusion of two patients due to statin therapy modification or discontinuation during follow-up, a final number of 31 patients were included. At a median follow-up of 32 (IQ1-3 30–37) days, 21 (67.7 %) patients reached their LDL-C target (primary endpoint). At 7 days, LDL-C mean value decreased from 123.6 ± 42.1 mg/dl to 97.9 ± 53.6 mg/dl, (p < 0.001), with a 29.9 ± 20.6 % reduction. At 32 days, LDL-C mean value declined to 58.5 ± 42.8 mg/dl (p < 0.001), with a 56.9 ± 20.9 % reduction. Conclusion: In a real-life single center population, inclisiran safely led to LDL-C target achievement within one month. Significantly reduction of LDL-C levels were already present in the early days after the first administration.